Impacts of injection pressure of a dip‐angle sloping strata reservoir with low porosity and permeability on CO2 injection amount. Issue 1 (25th July 2016) - Wang, Fugang; Jing, Jing; Yang, Yanlin; Liu, Hongyan; Sun, Zhaojun; Xu, Tianfu; Tian, Hailong
Abstract: Sloping strata reservoirs with low porosity and permeability are widely distributed in China. The first CO2 capture and geological storage (CCS) demonstration project in China that has been constructed in the Ordos Basin is a representative. In this paper, a 3D numerical model was constructed to evaluate the influence of injection pressure and strata dip angle on the CO2 injection amount in a sloping strata reservoir during CO2 injection period. We reached the following conclusions: (i) There is a 'balance time point (BTP)' for the total CO2 injection amount between a horizontal reservoir and a sloping one, and the BTP will decrease with the injection pressure increase. (ii) The influence of the dip angle of a sloping reservoir on the total injection amount is non‐monotonicity. For a fixed injection pressure, before the BTP, the greater the dip angle, the greater the CO2 injection amount, but after the BTP, the change rule is reversed. (iii) The injection pressure significantly affected the total injected CO2 amount, but the influence of the dip angle (in the range of 0° to 15°) on the total injection amount was not significant during injection. (iv) To a sloping reservoir, for long time injection (i.e., injection time is longer than the BTP), the bigger the dip angle, the greater the distance of the CO2 upward migration, and the smaller the total injected amount compared to the horizontal reservoir. So, in actual site selection of a CCS project, the small dip angle reservoir was beneficial. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd.